Cultural Hegemony of English Toward Americans as Seen in Wild Child Film by Nick Moore - Rabiatul Adawiyah; Darwina Darwina; Putri Utami; Sharah Rahmadhana; Dwi Rizki Angraini (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The present study aims to depict the hegemony and the way cultural hegemony influences cultural issues in Wild Child film. Therefore, the main data sources were the script of The Wild Child by Nick Moore and the book which tells the contents of the film. To collect the data, the researcher used library research. The qualitative descriptive was used to explore the issues found in this study. Based on the study, it was found that there are some norms found in which the English hegemonies to the American girl of the main character in this film. Those are norms, language, and values. The study also showed that the behavior of the main character â€œPoppyâ€ was influenced by the Americans. Based on the data result there are two (character, and attitudes) influenced of cultural Hegemony among the Americans and English in this film.